A dynamic systems approach to writing assessment in students with language learning problems. - Silliman ER; Jimerson TL; Wilkinson LC (Topics in Language Disorders, 2000)
Speech-language pathologists have not typically included writing as part of instructional or intervention goals. This omission may be related to the sparse research data on writing development in children with a language learning disability (LLD). Like reading and spelling, writing results from complex interactions among the linguistic and discourse systems and changes over time from an oral style of communication to a more literate style. One purpose of this article is to describe individual differences in the phases of writing development, drawing on examples from students who are typically developing, and those with an LLD. Special emphasis is given to the differentiation of audience and syntactic choices during the school-age years as critical elements in communicating the 'writer's voice.' Using an illustrative case study of a 10-year-old, the second purpose is to demonstrate how school-based writing samples can serve as a dynamic tool for analysis of interactions among the linguistic and discourse systems. The multiple levels addressed include genre knowledge, concept of audience, clausal and nonclausal complexity, spelling, and punctuation. A major assessment issue is whether the writing problems of individual students stem from an unrecognized LLD, instructional inadequacies, or both factors. Suggestions are offered for better meeting individual needs through combining explicit strategy instruction for composing and self-regulation with explicit linguistic strategies that enhance semantic and syntactic options in writing. Copyright © 2000 by Aspen Publishers, Inc.